Combined transabdominal and transvaginal ultrasound-guided percutaneous microwave ablation of uterine myomas: an effective monitoring technique. (31st December 2023) - Lin, Min; He, Jinghua; Lyu, Guorong; Li, Zuolin; Li, Xiaolian; Qiu, Sihua; Chen, Shujin; Zhang, Tingting; Wang, Jinyong; Li, Shuiping
Abstract: Objective: This study compared the feasibility and efficacy of transabdominal ultrasound (TAU) and combined transabdominal and transvaginal ultrasound (TA/TV US)-guided percutaneous microwave ablation (PMWA) for uterine myoma (UM). Method: This study enrolled 73 patients with UM who underwent PMWA via the transabdominal ultrasound-guided (TA group) or the combined transabdominal and transvaginal ultrasound-guided (TA/TV group) approaches. The intraoperative supplementary ablation rates, postoperative immediate ablation rates, lesion reduction rates and other indicators three months postoperatively were compared between the groups. The display of the needle tip, endometrium, uterine serosa, rectum and myoma feeding vessels under the guidance of TAU, transvaginal ultrasound (TVU) and TA/TV US were evaluated in the TA/TV group. Results: In the TA/TV group, the real-time position of the needle tip and the endometrium complete display rate of the same lesions with TVU guidance were significantly higher than those using TAU. TA/TV US guidance significantly improved the complete display rate of each indicator. The intraoperative supplementary ablation rate in the TA/TV group was lower than that in the TA group. Similarly, the postoperative immediate ablation and volume reduction rates of the lesions three months postoperatively were higher than those in the TA group, especially for lesions with a maximum diameter ≥6 cm. Conclusion: TA/TV US is an effective monitoring method that can be used to improve imaging display. Its use is recommended in patients with obesity, poor transabdominal ultrasound image quality and large myoma volumes.